2010
DOI: 10.1007/s11240-010-9834-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a ZmSERK gene and its relationship to somatic embryogenesis in a maize culture

Abstract: A SOMATIC EMBRYOGENSIS RECEPTOR KINASE (SERK) gene has been linked to somatic embryogenesis in many plant species. We have developed a culture model that enabled investigation of the relationship between embryogenesis and the expression of various ZmSERK genes at different developmental stages and following treatment with hormones. The results indicate that auxin 2,4-dichlorophenoxyacetic acid (2,4-D) enhanced transcription activity of ZmSERK and promoted somatic embryogenesis. The cytokinin 6-benzyladenine (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…The role of SERK in induction of somatic embryogenesis has been demonstrated in many plants, both monocots and dicots (Mahdavi-Darvari et al 2014). Zhang et al (2011) has reported expression of SERK in maize was closely related to auxin signaling during initial stages of somatic embryogenesis. The expression of SERK has been reported to be reduced in a gradual manner during subsequent development stages of somatic embryogenesis (Hecht et al 2001;Schmidt et al 1997), a trend which was observed in the present study too.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SERK in induction of somatic embryogenesis has been demonstrated in many plants, both monocots and dicots (Mahdavi-Darvari et al 2014). Zhang et al (2011) has reported expression of SERK in maize was closely related to auxin signaling during initial stages of somatic embryogenesis. The expression of SERK has been reported to be reduced in a gradual manner during subsequent development stages of somatic embryogenesis (Hecht et al 2001;Schmidt et al 1997), a trend which was observed in the present study too.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo gene expression patterns may reflect changes in culture media composition and assist in improvement of in vitro protocols. Screening of specific genes may also be useful to identify those that play a prominent role in controlling embryo development (Cairney and Pullman 2007;Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental systems for somatic embryogenesis are well established in some species (Raval and Chattoo 1993;Luo and Koop 1997;Nishiwaki et al 2000).Considerable efforts have been made during the past two decades to isolate and characterize genes involved in somatic embryogenesis (Lin et al 1996;Schmidt et al 1997;Zuo et al 2002;Aquea and Arce-Johnson 2008;Kiselev et al 2009;Montero-Cortes et al 2010;Zakizadeh et al 2010;Zhang et al 2011). Several genes encoding transcription factors have been isolated and identified in somatic embryogenesis.…”
Section: Introductionmentioning
confidence: 99%